SINGLE NUCLEOTIDE POLYMORPHISM DATA COMPARISON FOR GENETIC DIVERSITY AND GROUP STRUCTURE OF KOREAN NATIVE BLACK GOATS AND CROSSBRED GOATS - K. W. Kim; J. Lee; E. D. Lee; S. Kim; S. S. Lee; H. T. Lim andS. H. Lee (Journal of Animal and Plant Sciences, 2022)
We used single nucleotide polymorphism (SNP) data to investigate the genetic structure, diversity, and relationship between native and foreign cross bred goats. The Korean native black goat (KNBG) has four different strains; however, this differentiation is based solely on external factors. To differentiate KNBGs from foreign crossbred goats (CGs), we used the Illumina Goat SNP50K BeadChip to perform genome analysis. We found an SNP marker that could distinguish between breeds and strains of KNBGs, as well as between KNBGs and CGs. We extracted genetic data from 506 goats and identified 45,836 common SNPs. To identify the distinguishing SNPs, we calculated the allele frequency difference for each breed, and analyzed the absolute value of the frequency difference between randomly selected breeds using the top 10, 20, 30, 50, and 150 SNPs. The data were used to represent the genetic structure of KNBGs and CGs goats, and principal component analysis revealed a distinguishing marker between them. As the SNP value increased, the markers became more distinct. Our findings can provide insights into the genetic information about the KNBGs strains, and SNP data will serve as the basis for future genetic selection.
Keywords: Korea native black goat; genetic structure; genetic diversity; single nucleotide polymorphism